Combined high dose rate brachytherapy and external beam radiotherapy for clinically localised prostate cancer. Issue 2 (August 2018) - Strouthos, Iosif; Chatzikonstantinou, Georgios; Zamboglou, Nikolaos; Milickovic, Natasa; Papaioannou, Sokratis; Bon, Dimitra; Zamboglou, Constantinos; Rödel, Claus; Baltas, Dimos; Tselis, Nikolaos
Abstract: Purpose: To report the clinical outcomes and treatment-related toxicities after combined high-dose-rate (HDR) brachytherapy (BRT) with external beam radiotherapy (EBRT) for patients with clinically localised high-risk prostate cancer. Material and methods: Between 2008 and 2012, three hundred and three consecutive patients with organ-confined high-risk prostate cancer were treated with definitive radiotherapy consisting of HDR-BRT followed by supplemental EBRT. The transrectal 3D-ultrasound-based HDR-BRT boost consisted of two single-fraction implants of 10.5 Gy, prescribed to the 90% of the gland (D90), for a total physical dose of 21.0 Gy delivered to the prostatic gland. EBRT was delivered with conventional fractionation, prescribing 45.0 Gy to the prostatic gland and seminal vesicles. Biochemical failure was defined according to the Phoenix Consensus Criteria, genitourinary (GU)/gastrointestinal (GI) toxicity was evaluated using the Common Toxicity Criteria for Adverse Events (version 3.0). Results: The median follow-up was 71.6 months. The 7-year overall survival, biochemical control and metastasis-free-survival rates for the entire cohort were 85.7%, 88.3% and 93.8%, respectively. Androgen deprivation therapy was initiated prior to treatment for 92.7% of patients with a median duration of 12 months. Toxicity was scored per event with late Grade 2, 3 and 4 GU adverse events and was found to be 15.3%, 2.2% and 0.3%, respectively. Late Grade 2 GI toxicity accounted for 0.3% with no instances of Grade 3 or higher late adverse events. Conclusion: HDR-BRT with supplemental EBRT results in low biochemical relapse-free survival rates associated with a very low incidence of higher-grade late adverse events.